ARGUMENT - FRUNZĂ, Mihaela (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
This section groups several papers that illustrate the contemporary discussions in two subdisciplines of philosophy: phenomenology and formal logic. The first two papers, by Carmen Stadoleanu and Marius Florea, were presented at the Second International Conference of PhD Students in Philosophy, held in Cluj in May 22, 2022. Both papers were included in the Phenomenology & Hermeneutics section. Phenomenology and hermeneutics are two of the most complex and richest areas in contemporary philosophy. They both deal with the interpretation of human experience, and both have a long history in philosophy. Today, phenomenology and hermeneutics are still very important areas of philosophy, and they continue to be very intricate and rich. There are many different phenomenological and hermeneutical approaches, and each one has its own unique insights to offer.